The Global Crisis and Poverty - Kaya Halil Dincer (Studies in Business and Economics, 2018)
In this study, we examine the impact of the 2008-2009 Global Crisis on poverty rates across the globe. Our results are mixed. We find that, after the crisis, there was a marginally significant increase in the number of the poorest group of people (living on less than $1.25 a day at 2005 international prices) across the world. However, we do not find any significant increase in the number of people in the other low-income categories (living on less than $2, $2.50, $4, or $5). Although we do not find any significant increase in the poverty headcount ratios (the percentage of poor people in the population living on less than $1.25, $2, $2.50, $4, or $5), our results show that, interestingly, there has been a significant decrease in the national poverty headcount ratios (percentage of people living below the national poverty line which is based on estimates from household surveys) after the crisis. Overall, we suggest policymakers to focus on the poorest group of people during these hard times since this group is affected the most.